Assessing urbanization's contribution to warming in mainland China using satellite-estimated air temperature data. (October 2021) - Yao, Rui; Wang, Lunche; Huang, Xin; Wu, Xiaojun; Yang, Liu; Niu, Zigeng
The global surface air temperature (Ta) has increased significantly in the past several decades. However, it remains disputable how much effect rapid urbanization has had on warming trends in mainland China. In this study, a gridded Ta dataset was created using satellite data. Then, a series of satellite-based methods to evaluate the contribution of urbanization to warming were developed. Subsequently, the contribution of urbanization to warming during 2001–2018 was estimated. The national average Ta was found to have increased significantly (0.23°C/decade) in mainland China. At the national scale, the contribution of urbanization to warming was negligible (less than 1%) since built-up areas account for only approximately 2.66% of the area of China. At the regional scale, the contribution of urbanization was also small in most areas and was even negative in some areas. At the local scale, the contributions of urbanization to warming were 53.18%, 54.30% and 47.25% for the mean, maximum and minimum Ta, respectively, averaged for 31 major cities. This study demonstrated that the contribution of urbanization to warming was significant at the local scale, while the contribution of urbanization to large-scale warming was limited. The contribution of urbanization was underestimated at the local scale but overestimated at the national and regional scales by many previous studies due to the sparse and uneven distribution of meteorological stations.